(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main aim of this research is to investigate the differences between ESP and EGP classes for journalism faculties. Advantages and disadvantages of both types are learned and this article shares our conclusions.Besides, the needs of journalisms faculties’ students are analyzed, a questionnaire is designed, piloted and administered to 50 future journalists at Uzbekistan journalism and mass communications university. The results suggest that students refer to learn ESP which is appreciated as an effective way of learning professional terminology in English and improving reading, writing and translation skills which are used to a large extant in every day work by them.